The retrograde technique for recanalization of chronically occluded coronary arteries: case series report - Juričić, Stefan; Tešić, Milorad; Dobrić, Milan; Aleksandrić, Srdjan; Mehmedbegović, Zlatko; Stanković, Goran; Orlić, Dejan; Beleslin, Branko; Stojković, Siniša (Vojnosanitetski pregled, 2022)
Introduction. Chronic total occlusion (CTO) of the coronary artery still represents one of the most challenging lesion subsets in the field of interventional cardiology. Considering the complexity and increased risk posed by the retrograde approach, it is most often performed after a failed antegrade approach. Case report. We present a series of cases describing the retrograde approach as a special technique for treating CTO of the coronary artery. All cases had some special characteristics that are part of a dedicated portfolio in every catheterization lab today. In our series of cases, all three percutaneous coronary interventions (PCI) with a different strategies of the retrograde approach and supported with rotational atherectomy or intravascular ultrasound finished with successful recanalization of CTO. Conclusion. In cases where there is the presence of “interventional” collaterals, as well as when the antegrade approach is very difficult, the retrograde approach can increase the success rate of procedures. The retrograde approach requires a long learning curve as well as very skilled and experienced operators who are able to perform the procedure independently.